Completion of maternal and child health continuum of care and associated factors in West Gondar Zone, North West Ethiopia, 2023: a community based cross sectional study - Asrat Mekonnen Tegegne; Yohannes Ayanaw Habitu; Yeshiwas Ayale Ferede; Elsa Awoke Fentie (BMC, 2024)
Abstract Background The maternal and child health continuum of care integrates services from pre-pregnancy through childhood to enhance maternal and child outcomes. It is crucial for reducing maternal and child mortality by focusing on comprehensive health interventions. Despite its significance, comprehensive studies on the continuum remain limited. This study aimed to assess the completion of the maternal and child health continuum of care and associated factors among mothers with index children aged 12-23 months in the West Gondar Zone, Northwest Ethiopia, in 2023. Methods A community-based cross-sectional study was conducted from May 1-30, 2023, by interviewing mothers of 12-23-month-old children in West Gondar zone. A simple random sampling method was used to select 1,019 mothers. Data were collected via KoboCollect and analyzed in Stata version 14.0. Binary logistic regression was used to examine associations between independent variables and the continuum of care. Variables with a p value < 0.2 in bi-variable analysis were included in the multivariable model. Finally, adjusted odds ratios (AOR) with 95% confidence intervals (CI) and p values < 0.05 were used to determine statistical significance. The Hosmer and Lemeshow goodness-of-fit test was computed. Results The overall rate of completion of the maternal and child health continuum of care was 6.19% (95% CI: 4.69-7.68). The factors associated were having the first ANC visit before 16 weeks of pregnancy [AOR: 4.25 (CI: 2.14-8.47)], birth preparedness and complication readiness [AOR: 3.02 (CI: 1.41-6.46)], history of modern contraceptive use [AOR: 2.34 (CI: 1.16-4.73)], intended pregnancy [AOR: 3.25 (CI: 1.63-6.48)], receiving maternal services during ANC visits [AOR: 2.69 (CI: 1.07-6.80)], and the health facility being less than an hour away from home [AOR: 2.53 (CI: 1.06-6.03)]. Conclusions The maternal and child health (MCH) continuum of care in West Gondar was low. Key factors affecting completion included birth preparedness and complication readiness, early ANC initiation, planned pregnancy, family planning use, proximity to health facilities, and maternal health services provided during ANC. Efforts should target these factors and ensure services at each stage of the continuum to stay mothers along the path of the MCH continuum of care.